Die Bedeutung der Arbeit im Werk Adornos Impulse für eine kritische Soziale Arbeit - Reinisch, Konrad (Erziehung, Schule, Gesellschaft, 2021)
The reconstruction of the concept of labour in Adorno's work forms the basis of this volume. The book's recourse to, among others, Hegel and Marx, two decisive influences on Adorno's thinking, reveal a clear contrast through which Adorno's concept of work can be contoured particularly clearly. In the second part of the book, social work is examined against the backdrop of the considerations developed up to this point, and its proximity to the concept of integration through wage labour is elaborated. Based on this, reflections are made on what these results could mean for a concept of social work that regards itself as critical.